2010
DOI: 10.1111/j.1471-0528.2010.02567.x
|View full text |Cite
|
Sign up to set email alerts
|

What measured blood loss tells us about postpartum bleeding: a systematic review

Abstract: BackgroundMeta-analyses of postpartum blood loss and the effect of uterotonics are biased by visually estimated blood loss.ObjectivesTo conduct a systematic review of measured postpartum blood loss with and without prophylactic uterotonics for prevention of postpartum haemorrhage (PPH).Search strategyWe searched Medline and PubMed terms (labour stage, third) AND (ergonovine, ergonovine tartrate, methylergonovine, oxytocin, oxytocics or misoprostol) AND (postpartum haemorrhage or haemorrhage) and Cochrane revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 46 publications
1
51
0
Order By: Relevance
“…In a study investigating the efficacy of methylergonovine (which was less commonly used in the prevention of post-partum haemorrhage due to its side effects) in the control of bleeding, patients administered methylergonovine were compared with patients receiving 15-methyl PGF2a. While 15-methyl PGF2a was effective in the control of bleeding during the post-partum first hours, the performances of each of the drugs by the post-partum 3rd day showed both to be successful, with similar rates [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study investigating the efficacy of methylergonovine (which was less commonly used in the prevention of post-partum haemorrhage due to its side effects) in the control of bleeding, patients administered methylergonovine were compared with patients receiving 15-methyl PGF2a. While 15-methyl PGF2a was effective in the control of bleeding during the post-partum first hours, the performances of each of the drugs by the post-partum 3rd day showed both to be successful, with similar rates [9].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 17 studies, while the rate of post-partum haemorrhage varied between 4% and 51% without uterotonic treatment, it was shown that the rate of post-partum haemorrhage regressed to the following values with prophylactic oxytocin infusion, misoprostol treatment and ergometrine treatment, respectively: 0-32%, 1-45% and 0-37%. In the same study, the blood loss occurring with the administration of prophylactic uterotonic treatment was compared [9,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. It was found that this was reduced by an average of 151-499 mL in the patients administered with oxytocin, 155-433 mL in the patients administered with misoprostol and 149-476 mL in the patients administered with ergometrine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue is not whether WHO should keep misoprostol on the essential drug list, but rather who should be allowed access to misoprostol, which is an issue that each nation should decide, depending on its own national needs and priorities. 2 there is no excuse for the lack of awareness of the methodologically stringent review and meta-analysis, 3 which clearly demonstrates that methodologically sound studies find a substantial and highly significant benefit in the provision of misoprostol for postpartum haemorrhage prevention. The authors superficially discuss study quality while ignoring the valid implications thereof in their analysis and interpretation.…”
mentioning
confidence: 99%
“…Pathfinder might note that the Cochrane systematic review could not conduct a meta-analysis of community trials and comes to the same conclusion 'all four recent trials have design and setting differences that make the summing up of their results difficult.' 3 We identified randomized controlled trials of misoprostol in community and home setting from academic databases and systematic reviews and meta-analyses; our methods critically appraised study design, intervention and outcomes of these studies (see method section).…”
mentioning
confidence: 99%